A recyclable defluorination agent and preparation method thereof
By preparing a recyclable fluorine-removing agent composed of activated silicatic acid, organic polymer flocculants, deionized water and fluorine ion adsorbent, the existing fluorine-removing agents have been solved, and the coexisting pollutants of fluorine ions and heavy metal ions in sewage are effectively removed, which has significantly accelerated the sewage treatment speed and realized the recycling of resources.
Patent Information
- Application Number
- CN202411775503.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-10-12
AI Technical Summary
The existing fluorine-removing agents for sewage treatment have insufficient fluorine removal capacity and are single in control, so they cannot effectively remove the coexisting pollutants of fluorine ions and heavy metal ions in sewage.
Using a recyclable fluorine-removing agent composed of activated silicatic acid, organic polymer flocculants, deionized water and fluoride ion adsorbent, the fluoride ion adsorbent forms a hyperbranched polymer through cellulose-modified lanthanum montmorillonite and 1,3,5-triglycidyl-S-triazine trione structure to enhance adsorption capacity.
It significantly improves the removal efficiency of fluoride ions in sewage, and removes heavy metal ions, realizes coordinated control of multiple pollutants, significantly accelerates the sewage treatment speed, and makes the treated solids recyclable, realizing resource recycling.
Smart Images

Figure CN119430342B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fluorine-containing wastewater treatment, and in particular to a recyclable defluorination agent and a preparation method thereof. Background Art
[0002] With the development of science and technology and the acceleration of industrial progress, various emerging technologies have sprung up, greatly promoting the progress of productivity. However, in the context of rapid development, environmental pollution problems have become increasingly prominent. Among them, sewage discharge has become a major obstacle to development.
[0003] Fluoride ion is an element widely present in sewage, mainly from the electronics industry, chemical industry, metallurgy industry, electroplating industry and fertilizer production. High concentrations of fluoride ions discharged into water bodies will destroy the balance of aquatic ecosystems and affect the growth and reproduction of aquatic organisms. At the same time, high concentrations of fluoride ions will accumulate in the soil, reduce soil quality, and affect the growth and quality of crops. Long-term drinking of water with excessive fluoride content can cause diseases such as dental fluorosis and skeletal fluorosis in the human body. In severe cases, it can cause damage to organs such as the kidneys and liver, causing great harm to human health. Therefore, the removal of fluoride ions in sewage has become one of the problems that need to be solved urgently.
[0004] At present, most of the defluoridation agents on the market have a single function of removing pollutants, and their removal efficiency for fluoride ions is average. In the actual industrial production process, wastewater often contains multiple pollutants at the same time, among which metal ions and fluoride ions are common co-existing pollutants. The presence of metal ions also poses a threat to the environment and human health. The patent with announcement number CN110372075B discloses a high-efficiency defluoridation agent and its application. The agent is made of polyferric chloride, polyferric sulfate, polyaluminum ferric sulfate, polyaluminum chloride, tea iron, modified fly ash, modified zeolite, calcium hydrogen phosphate and a coagulant. Although the defluoridation agent has a fast removal speed and good effect for fluoride ions and has excellent defluoridation efficiency, the defluoridation agent prepared by the patent has a single object for pollutant control and cannot achieve the effect of synergistic control of multiple pollutants. Summary of the invention
[0005] The purpose of the present invention is to provide a recyclable defluorinating agent and a preparation method thereof, which solves the problem that the defluorinating capacity of defluorinating agents used in ordinary sewage treatment needs to be improved and the pollutant treatment is single.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A recyclable defluoridation agent comprises the following raw materials in parts by weight: 12-16 parts of activated silica, 150-200 parts of deionized water, 3-8 parts of organic polymer flocculant, and 18-22 parts of fluoride ion adsorbent;
[0008] The fluoride ion adsorbent is prepared by placing cellulose-modified lanthanum-loaded montmorillonite in N,N-dimethylformamide, fully mixing it, and then adding 1,3,5-triglycidyl-S-triazinetrione; the cellulose-modified lanthanum-loaded montmorillonite is prepared by placing lanthanum-loaded montmorillonite and carboxymethyl cellulose in deionized water, and adding a catalyst; the lanthanum-loaded montmorillonite is prepared by placing montmorillonite in anhydrous ethanol, fully mixing and stirring it, and then adding a lanthanum chloride solution, and reacting it in a water bath.
[0009] Furthermore, the organic polymer flocculant is polyacrylamide.
[0010] Furthermore, the preparation method of the fluoride ion adsorbent comprises the following steps:
[0011] S1: placing montmorillonite in anhydrous ethanol, stirring and mixing thoroughly, adding lanthanum chloride solution, heating to 80-85°C in a water bath for reaction for 2-3h, cooling, filtering and drying to obtain lanthanum-loaded montmorillonite;
[0012] S2: Place lanthanum-loaded montmorillonite and carboxymethyl cellulose in deionized water, ultrasonically disperse for 10-15 minutes, add p-toluenesulfonic acid, heat to 80-90°C, stir for 6-8 hours, cool, filter, and dry to obtain cellulose-modified lanthanum-loaded montmorillonite;
[0013] S3: Place the cellulose-modified lanthanum-loaded montmorillonite in N,N-dimethylformamide, mix and stir thoroughly, add 1,3,5-triglycidyl-S-triazinetrione and a catalyst, heat to 85-95°C for reaction for 5-6h, filter, wash and dry to obtain a fluoride ion adsorbent.
[0014] In this scheme, a lanthanum chloride solution is mixed with montmorillonite, and lanthanum-loaded montmorillonite is formed by heating in a water bath. Then, under the action of p-toluenesulfonic acid, the hydroxyl groups in the lanthanum-loaded montmorillonite interact with the carboxyl groups in the carboxymethyl cellulose structure to obtain cellulose-modified lanthanum-loaded montmorillonite. Then, under the action of a catalyst, the epoxy groups in the 1,3,5-triglycidyl-S-triazinetrione structure react with multiple active groups on the surface of the cellulose-modified lanthanum-loaded montmorillonite to obtain a fluoride ion adsorbent with a hyperbranched structure. The fluoride ion adsorbent has lanthanum-loaded montmorillonite as the core, and lanthanum ions are introduced into the interlayer of montmorillonite by ion exchange. Lanthanum ions have a high charge density and ionic radius, and can form a stable complex with fluoride ions, significantly enhancing the adsorption capacity of montmorillonite for fluoride ions. The lanthanum-loaded montmorillonite is modified by carboxymethyl cellulose to further enhance the adsorption capacity of montmorillonite, and 1,3,5-triglycidyl-S-triazinetrione is used to form a three-dimensional network hyperbranched polymer as the outer layer, so that the prepared fluoride ion adsorbent not only has a high degree of branching, forming multiple cavity structures, enhancing the adsorption surface area and adsorption sites, but also has a large number of hydroxyl groups in its structure, which can effectively complex heavy metal ions in sewage, such as calcium ions, magnesium ions, and aluminum ions. These metal ions can then combine with fluoride ions to form precipitates, thereby accelerating the removal of fluoride ions and the rate of sewage treatment. The adsorption properties of cellulose-modified lanthanum-loaded montmorillonite and the formed hyperbranched structure produce a synergistic effect, which jointly improves the adsorption capacity of fluoride ion adsorbents for fluoride ions. When added to the preparation process of the defluoridation agent, the prepared defluoridation agent has a large adsorption capacity and can quickly remove fluoride ions in sewage. At the same time, it also treats heavy metal ions in sewage, realizes the coordinated treatment of multiple pollutants, and can significantly improve the efficiency of sewage treatment. In addition, the precipitate after the defluoridation agent is saturated with adsorption has a recoverable value, which can realize the recycling of resources, effectively reduce the generation of waste, and contribute to the protection of water resources and the ecological environment.
[0015] Furthermore, in step S1, the mass fraction of the lanthanum chloride solution is 5-6%.
[0016] Furthermore, in step S1, the montmorillonite is calcium-based montmorillonite.
[0017] Furthermore, in step S2, the viscosity of the carboxymethyl cellulose is 800-1200 mpa·s.
[0018] Furthermore, in step S3, the catalyst is any one of tetrabutylammonium bromide, tetrabutylammonium chloride, and tetrabutylammonium hydroxide.
[0019] A method for preparing a recyclable defluorinating agent comprises the following steps:
[0020] Step 1, mixing activated silicic acid, organic polymer flocculant and deionized water, and stirring and mixing thoroughly to obtain a mixed solution;
[0021] Step 2: Add fluoride ion adsorbent to the mixed solution and stir for 0.5-2h to obtain a recyclable defluorination agent.
[0022] Furthermore, in step 1, the stirring rate of the sufficient stirring is 200-250r / min.
[0023] Furthermore, in step 2, the stirring rate of the stirring is 100-150 r / min. Beneficial effects of the present invention:
[0024] The present invention prepares a fluoride ion adsorbent and participates in the preparation process of the defluoridating agent, so that the prepared defluoridating agent has excellent adsorption capacity, can significantly improve the removal efficiency of fluoride ions in sewage, and at the same time, the defluoridating agent can also remove heavy metal ions in sewage, improve the possibility of coordinated treatment of multiple pollutants in sewage, greatly reduce the complexity of subsequent treatment, and significantly speed up the sewage treatment. In addition, the solids produced by filtering the treated sewage contain heavy metal ions and rare earth resources, which have excellent recoverable value, thereby realizing the recycling of resources, greatly reducing the environmental burden, and providing strong support for the protection of water resources and the environment.
[0025] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0027] Figure 1 This is a graph showing the sedimentation rates of the calcium-based montmorillonite and the lanthanum-loaded montmorillonite in the dispersion of the present invention. DETAILED DESCRIPTION
[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] The preparation methods of the fluoride ion adsorbents described in the following examples and comparative examples of the present invention are as follows:
[0030] S1: 5g of calcium-based montmorillonite was placed in 80ml of anhydrous ethanol, and after being fully stirred and mixed, 6ml of 5% lanthanum chloride solution was added, and the temperature was raised to 80°C for reaction in a water bath for 2h. After cooling, the montmorillonite was filtered and dried to obtain lanthanum-loaded montmorillonite;
[0031] 3g of calcium-based montmorillonite and lanthanum-loaded montmorillonite were placed in 150ml of toluene dispersion, and then ultrasonically dispersed for 10min before a sedimentation test. Figure 1 It can be seen that the sedimentation rate of calcium-based montmorillonite in the dispersion is very fast and it reaches sedimentation equilibrium within 3 hours. This is because the calcium-based montmorillonite has poor dispersibility and agglomeration occurs in the dispersion, which accelerates the sedimentation rate; the sedimentation rate of lanthanum-loaded montmorillonite in the dispersion is slow and it reaches sedimentation equilibrium within 6 hours, indicating that the dispersion performance of lanthanum-loaded montmorillonite is better. This is because the intercalation of lanthanum ions changes the structure and surface properties of montmorillonite, making its dispersion performance better.
[0032] S2: 5.8 g of lanthanum-loaded montmorillonite and 6 g of carboxymethyl cellulose with a viscosity of 800 mPa·s were placed in 120 ml of deionized water, ultrasonically dispersed for 10 min, 0.02 g of p-toluenesulfonic acid was added, the temperature was raised to 80°C and stirred for 6 h, and after cooling, the cellulose-modified lanthanum-loaded montmorillonite was filtered and dried;
[0033] S3: Place 6 g of cellulose-modified lanthanum-loaded montmorillonite in 120 ml of N,N-dimethylformamide, mix and stir thoroughly, then add 5 g of 1,3,5-triglycidyl-S-triazinetrione and 0.03 g of tetrabutylammonium bromide, heat to 85°C and react for 5 h, filter, wash and dry to obtain a fluoride ion adsorbent.
[0034] The nitrogen element analysis of cellulose-modified lanthanum-loaded montmorillonite and fluoride ion adsorbent using Vario MACRO elemental analyzer showed that cellulose-modified lanthanum-loaded montmorillonite contained almost no nitrogen, but the nitrogen content in the fluoride ion adsorbent was 7.26%. The appearance of nitrogen was due to the reaction between multiple active groups in the structure of cellulose-modified lanthanum-loaded montmorillonite and the epoxy groups in the structure of 1,3,5-triglycidyl-S-triazinetrione.
[0035] Example 1: Preparation of defluorinating agent
[0036] Step 1: Mix 12 parts of activated silicic acid, 3 parts of polyacrylamide and 150 parts of deionized water, and stir and mix them at a stirring rate of 200 r / min to obtain a mixed solution;
[0037] Step 2: Add 18 parts of fluoride ion adsorbent to the mixed solution, stir at a stirring rate of 100 r / min for 0.5 h to obtain a defluorination agent.
[0038] Example 2: Preparation of defluorinating agent
[0039] Step 1, 13 parts of activated silicic acid, 5 parts of polyacrylamide and 170 parts of deionized water were mixed, and the mixture was stirred at a stirring rate of 220 r / min to obtain a mixed solution;
[0040] Step 2: Add 19 parts of fluoride ion adsorbent to the mixed solution, stir at a stirring rate of 120 r / min for 0.8 h to obtain a defluorination agent.
[0041] Example 3: Preparation of defluorinating agent
[0042] Step 1: Mix 14 parts of activated silicic acid, 6 parts of polyacrylamide and 180 parts of deionized water, and stir and mix them at a stirring rate of 230 r / min to obtain a mixed solution;
[0043] Step 2: Add 20 parts of fluoride ion adsorbent to the mixed solution, stir at a stirring rate of 130 r / min for 1 hour to obtain a defluorination agent.
[0044] Example 4: Preparation of defluorinating agent
[0045] Step 1, 15 parts of activated silicic acid, 7 parts of polyacrylamide and 190 parts of deionized water were mixed, and the mixture was stirred at a stirring rate of 240 r / min to obtain a mixed solution;
[0046] Step 2: Add 21 parts of fluoride ion adsorbent to the mixed solution, stir at a stirring rate of 140 r / min for 1.5 hours to obtain a defluorination agent.
[0047] Example 5: Preparation of defluorinating agent
[0048] Step 1: Mix 16 parts of activated silicic acid, 8 parts of polyacrylamide and 200 parts of deionized water, and stir and mix them at a stirring rate of 250 r / min to obtain a mixed solution;
[0049] Step 2: Add 22 parts of fluoride ion adsorbent to the mixed solution, stir at a stirring rate of 150 r / min for 2 hours to obtain a defluorination agent.
[0050] Comparative Example 1: Preparation of defluorination agent
[0051] Step 1: Mix 14 parts of activated silicic acid, 6 parts of polyacrylamide and 180 parts of deionized water, and stir and mix them at a stirring rate of 230 r / min to obtain a mixed solution;
[0052] Step 2: Add 20 parts of calcium montmorillonite to the mixed solution, stir at a stirring rate of 130 r / min for 1 hour to obtain a defluorination agent.
[0053] Comparative Example 2: Preparation of defluorination agent
[0054] Step 1: Mix 14 parts of activated silicic acid, 6 parts of polyacrylamide and 180 parts of deionized water, and stir and mix them at a stirring rate of 230 r / min to obtain a mixed solution;
[0055] Step 2: Add 20 parts of lanthanum-loaded montmorillonite to the mixed solution, stir at a stirring rate of 130 r / min for 1 hour to obtain a defluorination agent.
[0056] Comparative Example 3: Preparation of defluorination agent
[0057] Step 1: Mix 14 parts of activated silicic acid, 6 parts of polyacrylamide and 180 parts of deionized water, and stir and mix them at a stirring rate of 230 r / min to obtain a mixed solution;
[0058] Step 2: Add 20 parts of cellulose-modified lanthanum-loaded montmorillonite to the mixed solution, stir at a stirring rate of 130 r / min for 1 hour to obtain a defluorinating agent.
[0059] Performance Testing
[0060] The defluoridation agents prepared in Examples 1 to 5 and Comparative Examples 1 to 3 were added as samples to the sewage to be treated, and magnetic stirring was carried out at 120 r / min for 45 min at 60°C. After the stirring was completed, the fluoride ion concentration in the treated sewage was determined by the selective electrode method. The results of the determination were graded. The fluoride ion concentration was less than 1 mg / L and was recorded as Grade A. The fluoride ion concentration was greater than or equal to 1 mg / L and less than 20 mg / L and was recorded as Grade B. The fluoride ion concentration was greater than or equal to 20 mg / L and less than 50 mg / L and was recorded as Grade C. The fluoride ion concentration was greater than or equal to 50 mg / L and was recorded as Grade D. The heavy metal ion concentration was detected using a JC-YZ-500 atomic absorption spectrophotometer. The fluoride ion concentration in the sewage to be treated was 1240 mg / L, and the content of heavy metal ions was 4658 mg / L. The main heavy metal ion components in the sewage to be treated were lead ions, mercury ions, cadmium ions, chromium ions and nickel ions. The specific test results are shown in the following table:
[0061]
[0062]
[0063] It can be seen from the above table that the defluoridants prepared in Examples 1 to 5 have excellent fluoride ion removal ability and high efficiency. The fluoride ion concentration in the sewage can be less than 1 mg / L within 45 minutes. At the same time, they also have excellent removal ability for various heavy metal ions, and can achieve the effect of removing various pollutants. The defluoridant prepared in Comparative Example 1 only uses calcium-based montmorillonite as an adsorbent, and the removal effect on both fluoride ions and heavy metal ions is limited, and the treatment effect on sewage is general. The defluoridant prepared in Comparative Example 2 uses lanthanum-loaded montmorillonite. Although lanthanum ions are loaded between montmorillonite layers, the adsorption performance of montmorillonite is increased, and it has a certain adsorption capacity for fluoride ions and heavy metal ions, but the treatment effect is not as good as that of the embodiment. In the sample prepared in Comparative Example 3, cellulose-modified lanthanum-loaded montmorillonite is added. Although the adsorption capacity of the defluoridant for fluoride ions and heavy metal ions is enhanced, the removal effect is still not as good as that of the embodiment.
[0064] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0065] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A recyclable defluorination agent, characterized in that: The invention comprises the following raw materials in parts by weight: 12-16 parts of activated silica, 150-200 parts of deionized water, 3-8 parts of organic polymer flocculant, and 18-22 parts of fluoride ion adsorbent; The organic polymer flocculant is polyacrylamide; The preparation method of the fluoride ion adsorbent comprises the following steps: S1: placing montmorillonite in anhydrous ethanol, stirring and mixing thoroughly, adding lanthanum chloride solution, heating to 80-85°C in a water bath for reaction for 2-3h, cooling, filtering and drying to obtain lanthanum-loaded montmorillonite; S2: Place lanthanum-loaded montmorillonite and carboxymethyl cellulose in deionized water, ultrasonically disperse for 10-15 minutes, add p-toluenesulfonic acid, heat to 80-90°C, stir for 6-8 hours, cool, filter, and dry to obtain cellulose-modified lanthanum-loaded montmorillonite; S3: Place the cellulose-modified lanthanum-loaded montmorillonite in N,N-dimethylformamide, mix and stir thoroughly, add 1,3,5-triglycidyl-S-triazinetrione and the catalyst, heat to 85-95°C for 5-6h, filter, wash and dry to obtain a fluoride ion adsorbent; The montmorillonite is calcium-based montmorillonite; The viscosity of the carboxymethyl cellulose is 800-1200mpa·s; The catalyst is any one of tetrabutylammonium bromide, tetrabutylammonium chloride and tetrabutylammonium hydroxide; In step S1, the mass fraction of the lanthanum chloride solution is 5-6%; The preparation method of the recyclable defluorination agent comprises the following steps: Step 1, mixing activated silicic acid, organic polymer flocculant and deionized water, and stirring and mixing thoroughly to obtain a mixed solution; Step 2: Add fluoride ion adsorbent to the mixed solution and stir for 0.5-2h to obtain a recyclable defluorination agent; In step 1, the stirring rate of the sufficient stirring is 200-250r / min; In step 2, the stirring rate of the stirring is 100-150r / min.
Citation Information
Patent Citations
A highly efficient defluorinating agent and its application
CN110372075B
Cellulose-based polymer / montmorillonite nano composite adsorption material and preparation method thereof
CN103263896A
Adsorbent containing aluminum / lanthanum pillared montmorillonite and preparation method of adsorbent
CN109847690A